Report of the Steering Committee : Fourteenth Meeting, 31 May - 2 June 2016, Višegrad, Bosnia and Herzegovina - European Cooperative Programme for Plant Genetic Resources; Bioversity International (2016)
The Fourteenth Steering Committee (SC) meeting of ECPGR took place in Višegrad, Bosnia and Herzegovina, from 31 May to 2 June 2016, hosted by the Ivo Andrić Institute and in collaboration with the University of Banjaluka. The meeting was attended by representatives from 34 countries and by observers from the Nordic Genetic Resource Center (NordGen), the European Seed Association (ESA), the European Association for Research on Plant Breeding (EUCARPIA), the Directorate-General for Environment (DG-ENV) of the European Commission, the FAO International Treaty for Plant Genetic Resources for Food and Agriculture (ITPGRFA) and the NGO Network for on-farm conservation and management.